Cytotoxic and xanthine oxidase inhibitory activities of chemical constituents of alphonsea cylindrica king - Mhd Bakri, Yuhanis; Abdulaimi, Ahmed Kareem Obaid; Syed Abdul Azziz, Saripah Salbiah; Nafiah, Mohd Azlan; Abdulla Aowda, Saadon; Hazim, Muhammad; Awang, Khalijah; Hashim, Yumi Zuhanis Has-Yun; Abbas, Phirdaous (A and V Publication, 2019)
This study aimed to investigate the chemical constituents from Alphonsea cylindrica as well as their cytotoxic and xanthine oxidase inhibitory activities. The chemical compounds were isolated and purified by various chromatographic techniques and their structures were elucidated via modern spectroscopic techniques including NMR, MS, IR, UV and comparison with literature. A study on the barks of A. cylindrica has found eleven known compounds were identified as stigmasterol (1), isoursuline (2), cyathocaline (3), kinabaline (4), muniranine (5), isooncodine (6), iraqiine (7), O-methylmoschatoline (8), kareemine (9), atherospermidine (10) and N-methylouregidione (11). The cytotoxic effect of hexane, DCM and methanol of bark of A. cylindrica as well as the isolated compounds; 1, 2, 3, 4, 5, 7, 8, 9 and 10 were estimated on MCF-7 human breast cancer cells and isoursuline possessed the most potent inhibitory activity with IC50 value of 33 µg/ml. Eight compounds 1, 3, 4, 5, 6, 8, 10 and 11 displayed moderate inhibitory activity effect with IC50 < 100 μM against xanthine oxidase. As a conclusion, eleven compounds have been isolated from the bark of A. cylindrica King. Some of the compounds also showed potential against cytotoxicity and xanthine oxidase inhibitory activities. The findings of this study can enhance the understanding of the chemotaxonomy aspect of the A. cylindrica as well as its potential in traditional and modern medicine